Characterisation of internal tremors and vibration symptoms - Harlan M Krumholz; Mitsuaki Sawano; Richa Sharma; Tianna Zhou; Dorothy Massey; Anna D Baker; Diana Berrent Güthe; Nick Güthe; Suzanne Pincus Shidlovsky; Liza Fisher; Connor B Grady; Cesar Caraballo (BMJ Open)
Objectives To describe the experiences of patients who have postacute sequelae SARS-CoV-2 infection with internal vibrations and tremors as a prominent component, we leveraged the efforts by Survivor Corps, a grassroots COVID-19 patient advocacy group, to gather information from individuals belonging to its Facebook group with a history of COVID-19 suffering from vibrations and tremors.Setting and design A narrative analysis was performed on 140 emails and 450 social media comments from 140 individuals collected as a response to a call to >180 000 individuals participating in Survivor Corps between 15 July and 27 July 2021. We used common coding techniques and the constant comparative method for qualitative data synthesis and categorising emails. Coded data were entered into NVivo V.12 to identify recurrent themes, theme connections and supporting quotations. Comments were analysed using Word Clouds, generated with R V.4.0.3 using quanteda, wordcloud and tm packages.Main outcome measures Patient-reported long COVID symptom themes and domains related to internal tremors and vibration.Results The respondents’ emails represented 22 themes and 7 domains pertaining to their experience with internal tremor and vibrations. These domains were as follows: (1) symptom experience, description and anatomic location; (2) initial symptom onset; (3) symptom timing; (4) symptom triggers or alleviators; (5) change from baseline health status; (6) experience with medical establishment and (7) impact on individuals’ lives and livelihood. There were 22 themes in total, each corresponding to one of the broader domains. Among the responses, many described symptoms that varied in location, timing and triggers, occurred soon after their COVID-19 infection, and were markedly debilitating. There were often frustrating experiences with the healthcare system.Conclusions This study describes key themes and experiences among a group of people reporting long COVID and having a prolonged and debilitating symptom complex that prominently features internal tremors and vibrations.